Comparison of two case difficulty assessment methods on cohorts of undergraduate dental students – a multi‐centre study. (11th September 2020) - Shah, P. K.; Duncan, H. F.; Abdullah, D.; Tomson, P. L.; Murray, G.; Friend, T. M.; Thomas, S.; Butcher, S.; Chong, B. S.
Abstract: Aim: To compare the educational benefits and user friendliness of two anonymized endodontic case difficulty assessment (CDA) methods. Methodology: A cohort ( n =  206) of fourth‐year undergraduate dental students were recruited from four different Dental Schools and divided randomly into two groups (Group A and B). The participants assessed six test endodontic cases using anonymized versions of the American Association of Endodontists (AAE) case difficulty assessment form ( AAE Endodontic Case Difficulty Assessment Form and Guidelines, 2006) and EndoApp, a web‐based CDA tool. Group A ( n =  107) used the AAE form for assessment of the first three cases, followed by EndoApp for the latter. Group B ( n =  99) used EndoApp for the initial three cases and switched to the AAE form for the remainder. Data were collected online and analysed to assess participants' knowledge reinforcement and agreement with the recommendation generated. Statistical analysis was performed using the two‐way mixed model anova, Cohen's Kappa (κ) and independent t ‐tests, with the levels of significance set at P <  0.05. Additionally, participants' feedback and preference for CDA was also gathered. Results: There was a significant increase in knowledge reinforcement for the AAE form and EndoApp ( P  = 0.001) after assessment of the first three test cases. However, this increase was not significant ( P  = 0.842) between the CDA methods. Overall, the AAE form and EndoApp had slight (κ = 0.176, P  < 0.001) and substantial (κ = 0.668, P  < 0.001) levels of agreement, respectively, and the difference was statistically significant ( P  < 0.001). Participants' feedback on user friendliness favoured EndoApp for all parameters measured. EndoApp was preferred by 65% of the cohort, whereas only 11% chose the AAE form for CDA. Conclusions: Both the AAE form and EndoApp were beneficial for dental education. EndoApp was reliable in helping with decisions to treat or refer, and combined with user friendliness, it was the preferred choice for CDA. Abstract : In this multi‐centre study, 206 fourth year dental undergraduate students, divided into two groups, assessed six Test Cases, containing clinical and radiographic information, using anonymised case difficulty assessment (CDA) tools. For cases 1–3, Group A ( n = 107) used the American Association of Endodontists form, whereas Group B ( n = 99) used EndoApp. CDA methods switched for the remaining cases. A strong preference for EndoApp was demonstrated. There was good agreement with participants' treat/refer decisions and CDA recommendations. Thus, EndoApp helped with decision‐making, and was the preferred CDA choice.